2016
DOI: 10.1002/hep.28572
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota profiling of pediatric nonalcoholic fatty liver disease and obese patients unveiled by an integrated meta‐omics‐based approach

Abstract: An Oscillospira decrease coupled to a 2-butanone up-regulation and increases in Ruminococcus and Dorea were identified as gut microbiota signatures of NAFL onset and NAFL-NASH progression, respectively. (Hepatology 2017;65:451-464).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

36
445
6
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 572 publications
(514 citation statements)
references
References 45 publications
36
445
6
5
Order By: Relevance
“…Importantly, it has been reported that improved intrahepatic TG content is related to a lower abundance of Firmicutes and a higher abundance of Bacteroidetes (45) (15). In support of these studies, pediatric patients with NAFLD showed an increase in Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea, and Ruminococcus and a decrease in Oscillospira and Rikenellaceae (44). Although it is clear that there may be some discrepancies in what defines dysbiosis in liver disease, the frequency of disease also occurs in association with obesity and is considered a manifestation of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 66%
“…Importantly, it has been reported that improved intrahepatic TG content is related to a lower abundance of Firmicutes and a higher abundance of Bacteroidetes (45) (15). In support of these studies, pediatric patients with NAFLD showed an increase in Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea, and Ruminococcus and a decrease in Oscillospira and Rikenellaceae (44). Although it is clear that there may be some discrepancies in what defines dysbiosis in liver disease, the frequency of disease also occurs in association with obesity and is considered a manifestation of metabolic syndrome.…”
Section: Introductionmentioning
confidence: 66%
“…166 Supporting these studies, pediatric patients with NAFLD had increased numbers of Bradyrhizobium, Anaerococcus, Peptoniphilus, Propionibacterium acnes, Dorea, and Ruminococcus, and decreased numbers of Oscillospira and Rikenellaceae. 167 In another study with adults, patients with NASH harbored a lower abundance of Faecalibacterium and Firmicutes (Clostridiales family, Anaerosporobacter) but a higher abundance of Parabacteroides and Allisonella in their fecal microbiomes. 168 Crucially, it has been reported that improved intrahepatic triglyceride content is related to a lower abundance of Firmicutes and a higher abundance of Bacteroidetes.…”
Section: Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Some bacterial strains, such as Escherichia coli, produce a significant amount of ethanol, which may reach the liver via the bloodstream in a continuous fashion and promote steatosis and liver injury [58]. Several studies assessed microbiome composition and fecal VOC composition in obesity related NAFLD [58][59][60].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…It was found that 12 fecal VOCS were significantly less, and 18 VOCs more abundant in NAFDL subjects (Table 3). Recently, Del Chierico and colleagues aimed to assess the structural and functional role of gut microbiota in onset and progression of pediatric NAFLD by analysis of fecal microbiota composition and bacterial derived fecal VOCs, by means of GC-MS-SPME [60]. In total, 61 children were included, comprising of 27 (NAFLD), 26 nonalcoholic steatohepatitis (NASH), 8 obese subjects without steatosis and 54 controls.…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%